Inverse association between remnant cholesterol and risks of atrial fibrillation among patients with type 2 diabetes - Jiang, Zeyu; Zhao, Kun; Sun, Mengqi; Sun, Jian; Pan, Shuhan (Frontiers in Endocrinology, 2025)
ObjectiveWe aimed to investigate the association between remnant cholesterol (RC) levels and the risk of atrial fibrillation (AF) among patients with type 2 diabetes, by leveraging data from a large cohort of diabetic patients.MethodsWe included patients with T2DM who received routine care at the affiliated hospital of Qingdao University between January 2014 and December 2023. A total of 9930 patients remained eligible for the final analysis. The primary outcome of this study was the incidence of atrial fibrillation.ResultsDuring a mean follow up of 6.12 ± 2.75 years, a total of 1,028 AF events occurred. Cox proportional hazards regression was performed to obtain the hazard ratios (HRs) for the incidence of atrial fibrillation by different RC levels at baseline. Compared to Q1, the age- and sex-adjusted HRs for coronary artery disease were 0.89 (95% CI: 0.80-1.28) in Q2, 0.88 (95% CI: 0.80-0.98) in Q3, and 0.76 (95% CI: 0.67-0.84) in Q4. As a continuous variable, RC had an HR of 0.77 (95% CI: 0.64-0.93). After adjusting for age, sex, systolic blood pressure, triglycerides, HbA1c, smoking status, eGFR, and the use of antiplatelet or anticoagulant, lipid-lowering, antihypertensive, and glucose-lowering medications, the multivariable-adjusted HRs were 0.92 (95% CI: 0.82-1.32) in Q2, 0.97 (95% CI: 0.88-1.08) in Q3, and 0.88 (95% CI: 0.79-0.98) in Q4. As a continuous variable, RC had an HR of 0.83 (95% CI: 0.66-0.99).ConclusionsWe demonstrated an inverse association between RC and incident risk of AF using data from real world retrospectively. Future prospective studies with the best option of an interventional trial are needed to further validate our findings.